2020
DOI: 10.6118/jmm.19024
|View full text |Cite
|
Sign up to set email alerts
|

Gold Thread Implantation for Female Sexual Dysfunction and Vaginal Laxity: A Preliminary Investigation

Abstract: Objectives: We evaluated the efficacy of gold thread implantation (GTI) in the vulva and vagina to improve female sexual dysfunction (FSD) and vaginal laxity. Methods: A retrospective chart review was conducted on 46 women who underwent GTI between 2017 and 2018 at our institution. Physicians interviewed patients using questionnaires at baseline and 1-3 months post-treatment. The questionnaires consisted of eight questions: vaginal laxity, vaginal dryness, pain during intercourse, sexual satisfaction during in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The International Consultation on Incontinence Questionnaire - Vaginal Symptoms (ICIQ-VS), electronic Personal Assessment Questionnaire for Pelvic Floor Disorders (ePAQ-PF), and Questionnaire for Diagnosing Open Vagina and Vaginal Flatulence (QUDOVVF) are validated questionnaires. Most of the studies used the Vaginal Laxity Questionnaire (VLQ 4 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 ; 16 studies), followed by other self-created questionnaires 26 27 28 29 30 31 32 33 34 35 36 37 (12 studies), ICIQ-VS 38 39 40 41 42 (5 studies), laser vaginal tightening 43 44 45 (3 studies), Visual Analog Scale (VAS 5 46 47 48 ; 4 studies), QUDOVVF 49 50 (2 studies), Patient Satisfaction Questionnaire 51 (1 study), Vaginal Functional Numeric Rating Scale (VFNRS 52 ; 1 study), and ePAQ-PF 1 (1 study).…”
Section: Resultsmentioning
confidence: 99%
“…The International Consultation on Incontinence Questionnaire - Vaginal Symptoms (ICIQ-VS), electronic Personal Assessment Questionnaire for Pelvic Floor Disorders (ePAQ-PF), and Questionnaire for Diagnosing Open Vagina and Vaginal Flatulence (QUDOVVF) are validated questionnaires. Most of the studies used the Vaginal Laxity Questionnaire (VLQ 4 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 ; 16 studies), followed by other self-created questionnaires 26 27 28 29 30 31 32 33 34 35 36 37 (12 studies), ICIQ-VS 38 39 40 41 42 (5 studies), laser vaginal tightening 43 44 45 (3 studies), Visual Analog Scale (VAS 5 46 47 48 ; 4 studies), QUDOVVF 49 50 (2 studies), Patient Satisfaction Questionnaire 51 (1 study), Vaginal Functional Numeric Rating Scale (VFNRS 52 ; 1 study), and ePAQ-PF 1 (1 study).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the Korean traditional medicine community has reported various side effects of GTT in patients with crow's feet [10], female sexual dysfunction and vaginal laxity [11] and patients wanting facial rejuvenation [7] who received GTT, and warned of the risk of secondary infection and intense pain after undergoing GTT in patients.…”
Section: Discussionmentioning
confidence: 99%
“…GTT can aid medical treatment when used correctly. It has been reported that GTT is therapeutic for Crow's feet in plastic reconstruction surgery [10] and has been reported to be effective for female sexual dysfunction and vaginal laxity in obstetrics and gynecology [11].…”
Section: Introductionmentioning
confidence: 99%